PENGARUH PELATIHAN DOUBLE LEG SPEED HOP DAN KNEE TUCK JUMP TERHADAP DAYA LEDAK OTOT TUNGKAI - Adhi Parthayasa, I Putu (Jurnal Ilmu Keolahragaan Undiksha, 2013)
This research aimed to determine the effect of double leg speed hops and knee tuck jump training in improving power of leg muscle. This research was a true experiment by the randomized pretest posttest control groups design. Samples taken by simple random sampling with a total samples were 45 students. Power of leg muscle was measured by vertical jump test and data were analyzed by independent t-test, one way anova and least significant difference (LSD) with significance level (Î±) 0,05 using SPSS 16.0. The results of using independent t-test showed that double leg speed hop and knee tuck jump training effective to improve the power of leg muscle with a significance value of 0,001 and 0,000 (Sig < 0,05). Based on one way anova and least significant difference (LSD) showed that there was a different effect between the two types of training in which knee tuck jump training have a better effect than double leg speed hops training with mean difference of 2,600. From the results, it could be concluded that double leg speed hop and knee tuck jump training were effective to improve power of leg muscle and there was a different effect between the two types of training and knee tuck jump training have a better effect than double leg speed hops training.